Extracellular space volume changes in the rat spinal cord produced by nerve stimulation and peripheral injury - Svoboda, J; Syková, E (Brain research, 1991)
Double-barrelled potassium and tetramethylammonium-sensitive microelectrodes were used in diffusion studies with tetramethylammonium ions, which remain essentially extracellular during the measurements. Activity-related changes in the extracellular space (ECS) volume fraction (alpha), ECS tortuosity (lambda) and the dynamics of the ECS volume changes were examined in the spinal dorsal horns of rats. The alpha and lambda in L4 and L5 segments of unstimulated rats were alpha = 0.24 +/- 0.01 (i.e. ECS occupied 24 +/- 1% of the total spinal cord volume) and lambda = 1.54 +/- 0.04 (mean +/- S.D. of mean, n = 21). The values were not significantly different throughout the dorsal horn. Repetitive electrical stimulation of peripheral nerves at 3-100 Hz increased extracellular potassium concentration [( K+]e) and ECS volume in Rexed laminae III-V by 15.8 +/- 2.7% (n = 5). After the end of stimulation, when the [K+]e decreased below the original baseline (K+ undershoot), the ECS volume decreased by 20-45%. The magnitude and duration of ECS volume decrease were positively related to the stimulation frequency and duration. The ECS volume decrease was maximal at 2-10 min after the stimulation had been discontinued, and it returned to the prestimulation values in 15-40 min. The ECS volume decreased by 20-50% after injury of the ipsilateral hind paw evoked either by subcutaneous injection of turpentine (n = 5), or by thermal injury (n = 6). The maximal changes were found in Rexed laminae III-V, 5-10 min after injection of turpentine and 10-25 min after thermal injury, and persisted for more than 120 min and 30 min, respectively.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: zadní končetina; Hindlimb; Rats; Spinal Cord; Peripheral Nerves; inbrední kmeny potkanů; extracelulární prostor; mícha; Electric Stimulation; Animals; zánět; zvířata; Rats, Inbred Strains; krysa rodu Rattus; ženské pohlaví; Inflammation; Female; periferní nervy; elektrická stimulace; Extracellular Space